DSP-0509, a systemically available TLR7 agonist, exhibits combination effect with immune checkpoint blockade by activating anti-tumor immune effects - Ota, Yosuke; Nagai, Yasuhiro; Hirose, Yuko; Hori, Seiji; Koga-Yamakawa, Erina; Eguchi, Ken; Sumida, Kentaro; Murata, Masashi; Umehara, Hiroki; Yamamoto, Setsuko (Frontiers in Immunology, 2023)
TLR7 is an innate immune receptor that recognizes single-stranded RNAs, and its activation leads to anti-tumor immune effects. Although it is the only approved TLR7 agonist in cancer therapy, imiquimod is allowed to be administered with topical formulation. Thus, systemic administrative TLR7 agonist is expected in terms of expanding applicable cancer types. Here, we demonstrated the identification and characterization of DSP-0509 as a novel small-molecule TLR7 agonist. DSP-0509 is designed to have unique physicochemical features that could be administered systemically with a short half-life. DSP-0509 activated bone marrow-derived dendritic cells (BMDCs) and induced inflammatory cytokines including type I interferons. In the LM8 tumor-bearing mouse model, DSP-0509 reduced tumor growth not only in subcutaneous primary lesions but also in lung metastatic lesions. DSP-0509 inhibited tumor growth in several syngeneic tumor-bearing mouse models. We found that the CD8+ T cell infiltration of tumor before treatment tended to be positively correlated with anti-tumor efficacy in several mouse tumor models. The combination of DSP-0509 with anti-PD-1 antibody significantly enhanced the tumor growth inhibition compared to each monotherapy in CT26 model mice. In addition, the effector memory T cells were expanded in both the peripheral blood and tumor, and rejection of tumor re-challenge occurred in the combination group. Moreover, synergistic anti-tumor efficacy and effector memory T cell upregulation were also observed for the combination with anti-CTLA-4 antibody. The analysis of the tumor-immune microenvironment by using the nCounter assay revealed that the combination of DSP-0509 with anti-PD-1 antibody enhanced infiltration by multiple immune cells including cytotoxic T cells. In addition, the T cell function pathway and antigen presentation pathway were activated in the combination group. We confirmed that DSP-0509 enhanced the anti-tumor immune effects of anti-PD-1 antibody by inducing type I interferons via activation of dendritic cells and even CTLs. In conclusion, we expect that DSP-0509, a new TLR7 agonist that synergistically induces anti-tumor effector memory T cells with immune checkpoint blockers (ICBs) and can be administered systemically, will be used in the treatment of multiple cancers.